2019
DOI: 10.1021/acsami.9b15180
|View full text |Cite
|
Sign up to set email alerts
|

Ten-Input Cube Root Logic Computation with Rational Designed DNA Nanoswitches Coupled with DNA Strand Displacement Process

Abstract: The predictability of Watson−Crick basepairing provides a unique structural programmability to DNAs, promoting a facile design of bimolecular reactions that perform computation. However, most of the current architectures could only implement limited logical circuits and are incapable of handling more complex mathematical operations, thus limiting computing devices from advancing to the next-stage functional complexity. Here, by designing a multifunctional DNA-based reaction platform coupled with multiple fluor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 32 publications
0
16
0
Order By: Relevance
“…Based on ref. 10, the calculation precision of the computation is measured by the relative error (RE).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on ref. 10, the calculation precision of the computation is measured by the relative error (RE).…”
Section: Resultsmentioning
confidence: 99%
“…5 The dynamic properties of DTMSD reactions strictly adhere to the Watson-Crick base pairing principle; 6 thus, the dynamic behavior of DTMSD is predictable and controllable. DTMSD is highly programable and can be cascaded to implement many sophisticated functions, such as logical computation, [7][8][9][10][11][12] analog computation, [13][14][15][16] biological sensors [17][18][19] and molecular walkers. [20][21][22] DTMSD circuits can be categorized as digital synthetic biological circuits and analog synthetic biological circuits.…”
Section: Introductionmentioning
confidence: 99%
“…The computing time of all circuits is within 10 minutes, showing the fastest complex DNA digital computing at present. Using DNA switches, Zhou et al [87] built a logic circuit that can compute the ten-input cube root (within 1000 decimals). It is a relatively large-scale logic system with 10 inputs and 4 outputs, demonstrating the power of DNA in the field of biological computing, and may bring new breakthroughs in the design of more complex computing circuits.…”
Section: Digital Computing Functionsmentioning
confidence: 99%
“…The computing time of all circuits is within 10 minutes, showing the fastest complex DNA digital computing at present. Using DNA switches, Zhou et al [87] . built a logic circuit that can compute the ten‐input cube root (within 1000 decimals).…”
Section: Computing Functions Realized With Sdrmentioning
confidence: 99%
“…In another paper, Zhou et al, constructed a logic circuit that can compute the cube root of a 10-bit binary number (within the decimal number 1000) for the first time. This research opened up a new vision for complex computing circuits and demonstrated the outstanding ability of DNA in the field of biological computing [ 13 ]. Fan et al, used DNA strand replacement technology to design a DNA-based switching circuit to implement digital computing, providing a new strategy for the development of molecular computers [ 14 ].…”
Section: Introductionmentioning
confidence: 99%